Effect of clients Strategic Index Case Testing on community-based detection of HIV infections (STRICT study). (September 2018) - Katbi, Moses; Adegboye, Adeoye; Adedoyin, Adefisayo; Yunusa, Fadimatu; Kayode, Gbenga; Bello, Maryam; Dakum, Patrick
Abstract: Background: Strategic Index Case Testing (STRICT), a form of partner notification service, was initiated to track, identify and notify sexual partners of people living with HIV (Index clients) with the sole aim of testing them to determine their HIV status and linking clients who are positive to Anti-Retroviral Therapy (ART). This research analyzed the HIV sero-prevalence among sexual partners of HIV positive clients using STRICT and determines the role of STRICT in HIV epidemic control. Methods: This is a non-control Interventional study that determined the impact of Strategic Index Case Testing (STRICT) on detecting previously undiagnosed HIV infections among sexual partners of positive index clients. This study was conducted in seven Local Government Areas (LGAs) of Karu, Nasarawa, Lafia, Doma, AMAC, Bwari, and Ushongo. These LGAs were selected for HIV epidemic control due to projected high prevalence of HIV from previous program level data. HTS was offered to sexual partners of index PLHIV from facility and community within the LGAs. Index clients were PLHIV diagnosed from outreaches, hot spots set up in strategic places and Provider Initiated Testing and Counseling (PITC) in comprehensive and primary health care facilities. Newly diagnosed PLHIV and those already enrolled and commenced on ART from October 2015 to July 2016 were identified from source registers. These index clients were counseled on how to notify their sexual partners about their HIV status and on bringing them for HIV Testing and Counseling (HTS). Those unable to do so after a given period of time were assisted by health workers in informing their various sexual partners based on the confidential agreement and informed consent signed by the Index clients. Findings: A total of 1277 index cases were counseled and interviewed with 879 index clients agreeing to disclosure, giving a disclosure rate of 68.3%. We identified 888 sexual partners from the interviews and traced 870 (97.9%) sexual contacts. A total of 741 (85.2%) of 870 sexual contacts traced were tested for HIV, out of which 378 (51%) tested positive using an HIV rapid test kit, and this was statistically significant at P Value = 0.0254. A total of 348 (92.1%) out of 378 HIV positive sexual partners were immediately commenced on ART using the recommended UNAIDS Test and Treat approach to HIV epidemic control. Interpretation: STRICT identifies the need for reaching out to sexual partners of index clients and providing them with HIV Testing Services (HTS) as they belong to a high risk priority population and also linking them to care and treatment. This group of people must be reached with HTS strategies in order to end the HIV epidemic as evidenced by high sero-prevalence of 51% among them.